Crystal structure of restriction endonuclease Kpn2I of CCGG-family - Manakova, Elena; Mikutenaite, Migle; Golovenko, Dmitrij; Gražulis, Saulius; Tamulaitiene, Giedre (Biochimica et biophysica acta. General subjects, 2021)
Restriction endonucleases belong to prokaryotic restriction-modification systems, that protect host cells from invading DNA. Type II restriction endonucleases recognize short 4–8 bp sequences in the target DNA and cut both DNA strands producing double strand breaks. Type II restriction endonuclease Kpn2I cleaves 5′-T/CCGGA DNA sequence (“/” marks the cleavage position). Analysis of protein sequences suggested that Kpn2I belongs to the CCGG-family, which contains ten enzymes that recognize diverse nucleotides outside the conserved 5′-CCGG core and share similar motifs for the 5′-CCGG recognition and cleavage. We solved a crystal structure of Kpn2I in a DNA-free form at 2.88 Å resolution. From the crystal structure we predicted active center and DNA recognition residues and tested them by mutational analysis. We estimated oligomeric state of Kpn2I by SEC-MALS and performed plasmid DNA cleavage assay to elucidate DNA cleavage mechanism. Structure comparison confirmed that Kpn2I shares a conserved active site and structural determinants for the 5′-CCGG tetranucleotide recognition with other restriction endonucleases of the CCGG-family. Guided by structural similarity between Kpn2I and the CCGG-family restriction endonucleases PfoI and AgeI, Kpn2I residues involved in the outer base pair recognition were proposed. Kpn2I is an orthodox Type IIP restriction endonuclease, which acts as a dimer. Kpn2I shares structural similarity to the CCGG-family restriction endonucleases PfoI, AgeI and PspGI. The Kpn2I structure concluded the studies of the CCGG-family, covering detailed structural and biochemical characterization of eleven restriction enzymes and their complexes with DNA. •The structure of Type IIrestriction endonuclease Kpn2I possessesPD-(D/E)XKfold.•Kpn2I belongs to the CCGG-family of restriction endonucleases.•Active center and DNA recognition residueswere confirmed by mutational analysis.•Kpn2I is an orthodox dimeric Type IIP restriction endonuclease.